2015
DOI: 10.3390/md13095722
|View full text |Cite
|
Sign up to set email alerts
|

Echinochrome A Improves Exercise Capacity during Short-Term Endurance Training in Rats

Abstract: Echinochrome A (Echi A) improves mitochondrial function in the heart; however, its effects on skeletal muscle are still unclear. We hypothesized that Echi A administration during short-term exercise may improve exercise capacity. Twenty-four male Sprague-Dawley rats were randomly divided into the following groups: control group (CG), Echi A-treated group (EG), aerobic exercise group (AG), and aerobic exercise treated with Echi A group (AEG) (n = 6 per group). Echi A was administered intra-peritoneally (0.1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
2
25
0
9
Order By: Relevance
“…Она развивается в результате много-кратной срочной адаптации к факторам среды большой интенсивности [17,18,19,21].…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Она развивается в результате много-кратной срочной адаптации к факторам среды большой интенсивности [17,18,19,21].…”
Section: Discussionunclassified
“…Он оказывает прямое антиоксидантное [1,4,12] и АТФ-сберегающее действие [19,25], активиру-ет систему глутатиона [23,24]. Гистохром при длительном введении увеличивает число мито-хондрий и их функциональную активность [18,19], поддерживает кальциевый гомеостаз клетки [12,13,19].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…7 Recent studies have revealed new insights into the mechanisms of cardioprotective 8 and acetylcholinesterase inhibitory 9 activities of echinochrome, as well as its ability to enhance mitochondrial biogenesis in cardiac 10 and skeletal muscles. 11 Also, some natural and synthetic hydroxynaphthazarins are potent antioxidants 12 and possess antiallergic activity. 13 Hydroxylated quinones are useful substrates for chemical modification.…”
Section: Introductionmentioning
confidence: 99%